2005
DOI: 10.1038/sj.jhh.1001948
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of primary hyperaldosteronism in mild to moderate hypertension without hypokalaemia

Abstract: Screening for primary hyperaldosteronism (PHA) is often indicated in individuals with resistant hypertension or hypokalaemia. However, in the far larger subset of the hypertensive population who do not fit into these criteria, the evidence for screening is conflicting and dependent on the disease prevalence. The purpose of this study was to examine the prevalence of PHA in a large population with mild to moderate hypertension and without hypokalaemia using a carefully controlled study protocol including a norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 43 publications
2
64
2
2
Order By: Relevance
“…Although this study 26 supports a much lower prevalence of PA than Rossi et al, 27 the data cannot be used as evidence for the prevalence in a nonselected population nor can the presence of APA be documented as it can be in some of the patients in the study by Rossi et al…”
Section: An Examination Of 2 Recent Seriescontrasting
confidence: 38%
“…Although this study 26 supports a much lower prevalence of PA than Rossi et al, 27 the data cannot be used as evidence for the prevalence in a nonselected population nor can the presence of APA be documented as it can be in some of the patients in the study by Rossi et al…”
Section: An Examination Of 2 Recent Seriescontrasting
confidence: 38%
“…confirmatory testing, would have confirmed positive for PA. The starting sample size of 296, however, was comparable to other primary care prevalence studies in which retention of subjects for further screening was low, and prevalence was similar to ours (13,21,22 Using a similar ARR cutoff as our study (ARR ≥ 25), they reported a 7.5% prevalence on screening. Although the prevalence in that study is similarly low to that demonstrated in our population, the U.K. study utilized a more stringent ARR cutoff for screening (ARR cutoff ≥ 40) (23).…”
Section: Discussionmentioning
confidence: 69%
“…Sindrom ini dilaporkan pertama kali pada tahun 1955 oleh Jerome W. Conn. 3 Sehingga, hiperaldosteronisme primer juga dikenal sebagai sindrom Conn. Pada saat ini, banyak laporan yang menunjukkan kejadian hiperaldosteronisme primer yaitu berkisar antara 3-20%. 4 Diagnosis sindrom Conn biasanya ditegakkan pada pasien dekade ketiga sampai keenam. Pada kasus ini, pasien mulai muncul keluhan di awal dekade ketiga dan sudah tiga kali dirawat di rumah sakit karena hipokalemia.…”
Section: Diskusiunclassified